Pengaruh Brand Ambassador Lee Min-Ho Terhadap Brand Awareness E-Commerce Lazada (Survei pada Pengikut @lazada_id) - Tabina Chairani Faridi; agustrijanto (UNIVERSITAS KALBIS, 2023)
The phenomenon of using actors and bands from South Korea as brand ambassadors is often busy being applied by many companies, one of which is a company in the e-commerce field, including the e-commerce company Lazada which uses Lee Min-Ho's brand ambassador. One of the goals in using a brand ambassador is to build brand awareness. So from the phenomenon that occurs, researchers want to find out the influence and how much influence Lee Min-Ho's brand ambassador has on Lazada's e-commerce brand awareness. The data was taken through distributing questionnaires to Instagram followers @lazada_id and the data was processed using Pearson Product Moment correlation analysis and simple linear regression. The results of this study are Lee Min-Ho's brand ambassador has a positive influence of 0.590 on Lazada's e-commerce brand awareness. In addition, the big influence given by brand ambassador Lee Min-Ho is 34.8% on Lazada's e-commerce brand awareness.